2018
DOI: 10.3390/nu10020158
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns Associated with Lower 10-Year Atherosclerotic Cardiovascular Disease Risk among Urban African-American and White Adults Consuming Western Diets

Abstract: The study’s objective was to determine whether variations in the 2013 American College of Cardiology/American Heart Association 10-year risk for atherosclerotic cardiovascular disease (ASCVD) were associated with differences in food consumption and diet quality. Findings from the baseline wave of Healthy Aging in Neighborhoods of Diversity across the Life Span (HANDLS) study 2004–2009, revealed participants consumed a Western diet. Diet quality measures, specifically the Healthy Eating Index (HEI)-2010, Dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 49 publications
(56 reference statements)
3
21
0
Order By: Relevance
“…However, the protective effects of the DASH dietary pattern from an increase in BMI with age were observed in the HANDLS study participants. Similarly, in this sample an inverse relationship between DASH score and 10 year atherosclerotic cardiovascular risk has also been reported [33].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, the protective effects of the DASH dietary pattern from an increase in BMI with age were observed in the HANDLS study participants. Similarly, in this sample an inverse relationship between DASH score and 10 year atherosclerotic cardiovascular risk has also been reported [33].…”
Section: Discussionsupporting
confidence: 75%
“…Results of multiple mixed-effects linear regression models indicated an inverse cross-sectional relationship between DASH (mean) and BMI (mean) , mainly in women and participants with incomes <125% of poverty. Previous research found that the food intake of this sample tended to resemble the Western diet, with low adherence to the DASH diet [33]. However, the protective effects of the DASH dietary pattern from an increase in BMI with age were observed in the HANDLS study participants.…”
Section: Discussionmentioning
confidence: 55%
“…Further, there are significant concerns about NOVA's actionability and practicality for various lifestyles, skill sets and resource availability. Studies comparing NOVA implementation with vetted plans such as DASH or MyPLATE are needed to show that nutrient intakes and health outcomes are at least equivalent to those from plans that promote the right balance of foods from all levels of processing (2,(72)(73)(74)(75)(76)(166)(167)(168)(169) .…”
Section: Resultsmentioning
confidence: 99%
“…Disparate intake of flavonoid classes by race could be a reflection of cultural food habits [ 11 , 58 ]. Previous research of HANDLS data has revealed food selections varied by race [ 39 , 54 ], which contributed to observed differences in dietary patterns with different 10-year atherosclerotic cardiovascular disease risk [ 39 ]. When compared to AA, W had higher mean Healthy Eating Index (HEI)-2010 scores for the total vegetables and whole fruits components [ 59 ], which would be consistent with W’s observed higher intakes of flavones and flavonols (both found primarily in vegetables) and anthocyanidins (found primarily in fruits, particularly berries and grapes).…”
Section: Discussionmentioning
confidence: 99%
“…Previously published research indicates the prevalence of risky health behaviors, including a nutrient-poor diet, is high among participants in HANDLS. For instance, Kuczmarski et al found that most HANDLS participants consume a pro-inflammatory Westernized diet [ 39 ]. The Westernized diet is characterized by high intakes of saturated fat, proteins (derived from processed meats), and sugars and low intakes of dietary fiber [ 40 ].…”
Section: Introductionmentioning
confidence: 99%